Indonesian EFL Students’ Perception of Online Learning as Expressed through Metaphors - Pardede, Parlindungan (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2023)
Language learning can get two essential benefits from metaphor, as it is an effective tool for language learning and a useful tool for revealing abstract, obscure, and tacit ideas. One of the most problematic phenomena in education today is online learning (OL). Although all higher learning institutions have adopted it for almost three years, OL is still far from being effective. To get a better understanding of OL, this study aims at exploring EFL students’ experience and perception of OL employing metaphor analysis. Involving 69 students of a private university in Jakarta, Indonesia, data was collected online through Google Form in which the participants were asked to complete a sentence running “Online learning is like … because ….” The gathered metaphors were then analyzed using the content analysis procedures. The results showed the most predominantly metaphors produced by the participants are positive (32 items), followed by negative metaphors (25 items), and neutral metaphors (2 items). Based on the discussions, some suggestions are recommended for further research and OL practices improvement.